2000
DOI: 10.1200/jco.2000.18.9.1921
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Gemcitabine Plus Cisplatin in Patients With Metastatic Urothelial Cancer

Abstract: Gemcitabine plus cisplatin is active in the treatment of metastatic urothelial cancer in chemotherapy-naive patients and has an acceptable clinical safety profile. Studies are under way to further define the place of gemcitabine in combination with other chemotherapeutic agents in the treatment of metastatic urothelial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
82
0
10

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(99 citation statements)
references
References 16 publications
7
82
0
10
Order By: Relevance
“…The objective has been to find combinations that demonstrate improved efficacy and a better toxicity profile compared with that of M-VAC. The most extensively studied drugs have been gemcitabine (Moore et al, 1999;Von der Maase et al, 1999;Kaufman et al, 2000) and paclitaxel (Redman et al, 1998;Vaughn et al, 1998;Zielinski et al, 1998;Dreicer et al, 2000;Small et al, 2000), each in combination with cisplatin or carboplatin. These studies have usually shown an elevated activity with a favourable toxicity profile (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The objective has been to find combinations that demonstrate improved efficacy and a better toxicity profile compared with that of M-VAC. The most extensively studied drugs have been gemcitabine (Moore et al, 1999;Von der Maase et al, 1999;Kaufman et al, 2000) and paclitaxel (Redman et al, 1998;Vaughn et al, 1998;Zielinski et al, 1998;Dreicer et al, 2000;Small et al, 2000), each in combination with cisplatin or carboplatin. These studies have usually shown an elevated activity with a favourable toxicity profile (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies using GC for treating urothelial cancer have been done. Kaufman et al (19), reported an overall response rate of 41% (CR: 22%, PR: 19%), a median time to treatment failure of 5.5 months and a median overall survival of 14.3 months for the metastatic urothelial cancer patients who were treated with GC. Moore et al (20), reported that using GC for advanced urothelial cancer produced an overall response rate and a median survival of 57% (CR: 21%, PR: 36%) and 13.2 months, respectively, which concurs with our findings of an overall response rate and a median survival of 36% (CR: 24%, PR: 12%) and 20 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 New agents, including gemcitabine, [7][8][9][10] paclitaxel, 11 and docetaxel, 12 have shown activity in patients with bladder and urinary tract transitional cell carcinomas. In Phase II trials, gemcitabine has been combined successfully with cisplatin, [13][14][15] paclitaxel, 16 and paclitaxel plus carboplatin, 17 producing interesting response rates and median survivals. A recently published multicenter, randomized study comparing M-VAC with gemcitabine plus cisplatin (GC) documented no differences in activity, progression free survival, and overall survival, with a tolerability profile favoring GC.…”
mentioning
confidence: 99%